Constant frequency, non‐isolated multichannel LED driver based on variable inductor. Issue 8 (26th April 2021) - Liang, Guozhuang; Tian, Hanlei; Wang, Hetong; Xia, Yiwen; Xiao, Xianyong
Abstract: To obtain the required LED‐driving current, variable frequency control directly leads to large reactive circulation, and the design of the electromagnetic interference circuit is more complex. However, soft switching cannot be guaranteed by constant frequency operation under load variations. Hence, a multiplex LED‐dimming circuit based on a variable inductor is proposed that completes the constant frequency operation and realizes zero‐voltage switching to improve efficiency. The proposed circuit with a superimposed half‐bridge structure increases the number of outputs and simultaneously shares the resonant inductor so that the power density is improved and the LED‐dimming unit is simplified. The working principle of the circuit is described—it uses eight‐channel output to build an 80 W experimental prototype to verify the feasibility of the LED driver.